Effect of storage time on mirror carp (Cyprinus carpio L) pastrami stored in market temperature - Arslan, A; Gonulalan, Z; Celik, C (Scientific Technical Research Council Turkey, 1997)
The aim of this study was to determination of microbiological and chemical properties and effect of vacuum during storage period of vacuumed and unvacuumed Mirror carp (Cyrinus carvio L.) pastrami. Pastrami samples produced experimentally and stored in market (20 degrees C) conditions. 0, 7, 14, 21, 30, 45, 60, 90 and 120(th) days of maturity analysis were performed. Unvacuumed pastrami samples analysis had been until 45(th) day of maturity due to lose high amount of moisture. In microbiologic analysis number of bacteria were decreased during storage period. in vacuumed pastrami samples numbers of viable aerobes, anaerob microorganisms, psychrophiles, lactobacillus, Staphylococcus - Micrococcus, yeast and molds were between 1.8 x 10(4) - 9.1 x 10(5) cfu/g; 7.4 x 10(3) - 7.1 10(5) cfu/g; 0 - 3.6 x 10(2) Cfu/g; 6.6 x 10 - 1.4 x 10(4) cfu/g; 6.5 10(3) - 1.5 x 10(5) Cfu/g; 0 - 2.3 x 10(2) cfu/g and in unvacuumed pastrami were between 1.5 x 10(3) - 8.9 x 10(5) cfu/g; 7.1 x 10(2) - 3.6 x 10(5) Cfu/g: 0 - 9.6 x 10 cfu/g; 9.5 x 10 - 1.3 10(3) cfu/g; 2.3 x 10(2) - 6.0 x 10(4) Cfu/g; 0 - 4.0 x 10 cfu/g; respectively. Coliforms were not noticed in both vacuumed and unvacuumed pastrami samples. Differences in viable aerobes on 14, 21, 45(th) days, in anaerob microorganisms and Staphylococcus - Micrococcus on 30, 45(th), in Lactobacillus on 45(th), in yeasts and melds first and 14(th) days of maturity were significant between pastrami samples (p<0.05). During the storage period pH levels were decreased in vacuumed and unvacuumed pastrami samples. Moisture consent were decreased in unvacuumed pastrami samples. Moisture, fat, ash, salt and pH values in vacuumed pastrami samples were between 32.48 - 36.81%; 6.33 - 8.42%; 9.75 - 11.94%; 8.33 - 12.91%; 5.41 - 5.92 and unvacuumed pastrami same values were between 15.96 - 38.13%; 7.77 - 14.88%; 5.51 - 15.60%; 7.75 - 14.68%; 5.65 - 5.95 respectively. Statistically, the differences between both vacuumed and unvacuumed pastrami samples for moisture on 7, 14, 21, 30 and 45(th), for fat content on 7, 30 and 45(th) days of maturity, for salt con-lent first and 30(th) days, for ash content during the storage period were significant (p<0.05). In conclusion microbiologic and chemical results indicated that vacuumed mirror carp pastrami samples keeps quality characteristics at least 120 days of storage in market temperature.
Keywords: fish; pastrami; temperature; microbiologic; chemical; quality